RANCANG BANGUN SISTEM KEAMANAN SEPEDA MOTOR DENGAN SENSOR SIDIK JARI - Tatik Juwariyah; Alina Cynthia Dewi (Bina Teknika, 2017)
The high cases of motor vehicle theft, especially motorcycles theft became a daily problem that still need to look for solution. One of the solutions for securing a motorcycle from theft is by applying intellegent security system technology. The purpose of this research was to design motorcycle security system with fingerprint sensor and determine the percentage of sytem design success. The research methods used are designing, formulating problem and studying literature. The next step are to design the system design and assemble the design. The first was a registered the fingerprint owner motorcycle in order recorded in the data system. The second was to match the fingerprint registered. The design assembly consists of power supply, arduino UNO microcontroller module, fingerprint module, LED and relay module which would be connected with the electrical system motorcycle. Next step was to install the prototype on the motorcycle that connected the relay module with the wire between switch of side buffer and the machine of motorcycle. The result of the triasl system with Thirteen the user motorcycle his fingerprints was not registered indicates system 100% seccess. This means even though the key contact in the ON position the motorcycle could not be turned on by front starter or side starter(engkol). The only the fingerprint registered that could be turned on the machine of motorcycle.